INDONESIAN INHERITANCE SYSTEM BASED ON ISLAMIC LAW, CIVIL CODE, MATRILINEAL CUSTOMS, AND GENDER EQUALITY PERSPECTIVES - Achmad Gusti Malayudha; Widya Sari; Angga Puja Asiandu (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2023)
In this article, the author discussed the inheritance system in Indonesia. The inheritance distribution system in Indonesia is based on Islamic law, civil code, and customary law. On the other hand, gender equality activists have their perspectives regarding the justice of the distribution system based on the proportion received by men and women. Based on the discussion, it was known that there are similarities and differences among Indonesian inheritance distribution systems. Each of the systems regulates that the testator must die and the main heirs are blood-related to the decedent. In Islam law, men receive more than a woman with a ratio ofÂ 2:1 due to menâ€™s responsibility to their family. Meanwhile, the proportion between men and women regulated by the Indonesian civil code is equal. In Minangkabau matrilineal customary law, as a system based on the mother's lineage, the proportion of inheritance is distinguished between high inheritance and low inheritance. The high inheritance will be given to the woman and the low inheritance will be shared equally between men and women. However, some gender equality activists might see those proportions as a form of injustice. But, each of the systems has its perspective regarding justice.